Impact of Reviewing Procedure With Visual Gaze Patterns on Improving Endoscopic Submucosal Dissection Skills - Huy Thanh Dang; Fumiaki Ishibashi; Kosuke Okusa; Kentaro Mochida; Takao Tonishi; Sho Suzuki (JGH Open, 2025)
ABSTRACT Aims No previous studies have reported on whether tracking and reviewing physicians' gaze patterns affect the endoscopic submucosal dissection (ESD) training process. This study investigated differences in physicians' gaze patterns during ESD and assessed how reviewing their procedure afterward impacted ESD skills. Methods and Results The gazing points of three trainees during mucosal incision, submucosal dissection, and hemostasis were captured and recorded using the eye‐tracking device. Fifteen short video clips were created from six recorded videos. Three trainees and two expert endoscopists later reviewed these video clips. Key outcomes included: (1) time spent gazing at the appropriate mucosal incision direction, (2) time spent gazing at the appropriate submucosal dissection line, and (3) time required to identify bleeding points. During video review, the trainees spent significantly more time fixating on the appropriate mucosal incision direction than during live performance (24.9 s vs. 6.4 s, p < 0.01). However, this was still shorter than expert reviewers (28.4 s, p < 0.01). Similarly, the trainees spent more time observing the appropriate submucosal dissection line during review than in real‐time (12.9 s vs. 4.8 s, p < 0.05), with no significant difference compared to the experts (14.6 s, p = 0.66). However, there was no significant difference in time to identify the bleeding point between review and real‐time performance (9.3 s vs. 11.4 s, p = 1.00). Conclusion This pilot study suggests that video‐based review with eye‐tracking feedback may help trainees adopt expert‐like visual strategies during ESD, potentially enhancing procedural performance.